Compositional evaluation of lesion and parent bone in patients with juvenile osteochondritis dissecans of the knee using T2* mapping. Issue 7 (20th October 2021) - Zbýň, Štefan; Santiago, Cassiano; Johnson, Casey P.; Ludwig, Kai D.; Zhang, Lin; Marette, Shelly; Tompkins, Marc A.; Nelson, Bradley J.; Takahashi, Takashi; Metzger, Gregory J.; Carlson, Cathy S.; Ellermann, Jutta M.
Abstract: Juvenile osteochondritis dissecans (JOCD) lesions contain cartilaginous, fibrous and osseous tissues which are difficult to distinguish with clinical, morphological magnetic resonance imaging (MRI). Quantitative T 2 * mapping has earlier been used to evaluate microstructure and composition of all aforementioned tissues as well as bone mineral density. However, the ability of T 2 * mapping to detect changes in tissue composition between different JOCD lesion regions, different disease stages, and between stable and unstable lesions has not been demonstrated. This study analyzed morphological and T 2 * MRI data from 25 patients (median age, 12.1 years) with 34 JOCD‐affected and 13 healthy knees. Each lesion was assigned a stage reflecting the natural history of JOCD, with stages I and IV representing early and healed lesion, respectively. T 2 * values were evaluated within the progeny lesion, interface and parent bone of each lesion and in the control bone region. T 2 * was negatively correlated with JOCD stage in progeny lesion ( ρ = −0.871; p < 0.001) and interface regions ( ρ = −0.649; p < 0.001). Stage IV progeny showed significantly lower T 2 * than control bone ( p = 0.028). T 2 * was significantly lower in parent bone than in control bone of patients with stable lesions ( p = 0.009), but not in patients with unstable lesions ( p = 0.14). Clinical significance: T 2 * mapping enables differentiation between different stages of JOCD and quantitative measurement of the ossification degree in progeny lesion and interface. The observed T 2 * decrease in healed and stable lesions may indicate increased bone density as a result of the active repair process. T 2 * mapping provides quantitative information about JOCD lesion composition.